OPTIMALISASI POTENSI TENAGA KERJA LOKAL MELALUI PELATIHAN REKRUTMEN DAN PENGEMBANGAN SDM DI PAUH, KOTA PADANG - Suhanda, Mya Yuwanita; Yulihardi, Yulihardi; Febriani, Rina; Suandi, Edi; Afrida, Afrida (Komunitas Manajemen Kompetitif, 2024)
Pauh District, Padang City, has a large local workforce potential, but its utilization by businesses and MSMEs is not yet optimal. The main problems include the low match between workforce competencies and business needs, the informal recruitment process, and a lack of understanding of sustainable human resource development. This condition has resulted in low local workforce absorption and less than optimal business productivity. This Community Service Program aims to optimize the potential of the local workforce through structured, applicable recruitment and human resource development training based on the real needs of the business world. The approach used is participatory and empowering, involving businesses and workers at every stage of the activity. Implementation methods include needs identification, practice-based training, case study discussions, and ongoing mentoring with materials tailored to the characteristics of local MSMEs. The program outputs include training models based on local potential, increased workforce competency, and strengthened managerial capacity of business actors. In the long term, this program is expected to increase business competitiveness and strengthen the local economy in a sustainable manner